Rebuilding the urban structure of the inner city : a strategy for the repair of downtown Oakland, Calfornia - Peter Bosselmann; Stefan Pellegrini (University of California, Institute of Urban and Regional Development (IURD), 2003)
American cities have struggled to maintain the centrality of their downtown areas. As retail and office uses have continued to move into suburban areas and outlying regions, many local governments - especially of smaller and mid-size cities - have all but given up on the prospect of replacing the commercial vitality once found in many city centers. The ability to attract a permanent residential population, lured by good regional access, has become a necessary prerequisite for attracting new commercial uses back to the inner city.
Keywords: 330